Efficacy of a single oral dose of a live bivalent E. coli vaccine against post-weaning diarrhea due to F4 and F18-positive enterotoxigenic E. coli. (August 2017) - Nadeau, É.; Fairbrother, J.M.; Zentek, J.; Bélanger, L.; Tremblay, D.; Tremblay, C.-L.; Röhe, I.; Vahjen, W.; Brunelle, M.; Hellmann, K.; Cvejić, D.; Brunner, B.; et al.
Highlights: A single live oral bivalent F4/F18 vaccine was administered to pigs in drinking water. Vaccination prevented post-weaning diarrhea due to F4-enterotoxigenic E. coli (ETEC) infection and F18-ETEC in pigs within 7 days. Oral bivalent F4/F18 vaccine reduced faecal shedding of F4-ETEC and F18-ETEC and resulted in heavier pigs. Cross-protection of the F18ac vaccine strain against F18ab- E. coli pathogenic strain was demonstrated by challenge. Oral bivalent F4/F18 vaccine elicited specific anti-F4 and anti-F18 IgM and IgA. Abstract: F4- and F18-positive enterotoxigenic E. coli strains (F4-ETEC and F18-ETEC) are important causes of post-weaning diarrhea (PWD) in pigs. F4 (antigenic variant ac) and F18 (ab and ac) fimbriae are major antigens that play an important role in the early stages of infection. Herein, the efficacy of a live oral vaccine consisting of two non-pathogenic E. coli strains, one F4ac- and one F18ac-positive, was evaluated using F4ac-ETEC and F18ab-ETEC challenge models. A randomized, masked, placebo-controlled, block design, parallel-group confirmatory study with two different vaccination-challenge intervals (7 and 21 days) was conducted for each challenge model. The vaccine was administered in one dose, to ≥18-day-old piglets via drinking water. Efficacy was assessed by evaluating diarrhea, clinical observations, weight gain and fecal shedding of F4-ETEC or F18-ETEC. Anti-F4 and anti-F18 immunoglobulins in blood were measured. The vaccination resulted in significant reductions in clinical PWD and fecal shedding of F4-ETEC and F18-ETEC after the 7- and 21-day-post-vaccination heterologous challenges, except for after the 21-day-post-vaccination F4-ETEC challenge, when the clinical PWD was too mild to demonstrate efficacy. A significant reduction of mortality and weight loss by vaccination were observed following the F18-ETEC challenge. The 7-day protection was associated with induction of anti-F4 and anti-F18 IgM, whereas the 21-day protection was mainly associated with anti-F4 and anti-F18 IgA. The 7-day onset and 21-day duration of protection induced by this vaccine administered once in drinking water to pigs of at least 18 days of age were confirmed by protection against F4-ETEC and F18-ETEC, and induction of F4 and F18-specific immunity. Cross protection of the vaccine against F18ab- E. coli was demonstrated for both the 7- and 21-day F18-ETEC challenges.